Growht of infants aged 0-12 months in severe iodine deficient areas - Diet Sadiah Rustama (Indonesian Pediatric Society, 1999)
In lndonesia, iodine deficiency remains a public health problem and iodine deficiency disorder (lDD) Control Programs are not optimally implemented. This situation might affect the growth and development of young infants living in iodine deficient areas. Eight hundred and eight infants aged 0-12 months in 5 severe iodine deficient subdistrics in West Java, were studied to assess their linear growth. Using the US National Center for Health Statistics (NHCS) age reference standards, there were 14.7% of infants with Z-score below 2 SD of the mean for normal height, defined as stunted. Using the local standards there were 8.2% of infants with stunted growth. The percentage of stunted infants were significantly higher with increasing age. The stunted infants among goitrous mothers were higher compared to those among non-goitrous mothers. It was concluded that a relatively high percentage of linear growth impairment in this study might be attributable to iodine deficiency or other factors. The infants of mothers with goiter were at higher risk of being stunted.